Transdisciplinary methodologies for cultural sustainability in Fashion Design (Revista de Ensino em Artes, Moda e Design, 2025)
This article offers a theoretical-methodological reflection on the role of transdisciplinarity in fashion design education, with a focus on valuing artisanal practices, the relationships between designers and artisans, and cultural sustainability in fashion design through the development of culturally sensitive educational practices—that is, practices that recognise, respect, and incorporate the sociocultural contexts of the individuals involved. Drawing on the distinction between multidisciplinary and transdisciplinary approaches, the study adopts a qualitative and critical methodology to analyse four teaching methodologies: participatory design, cultural storytelling, project-based learning, and systemic learning, organised around three structuring axes: methodological, strategic, and validation. The systematisation of these approaches, presented via an analytical framework comprising design tools, modes of practical application, and expected outcomes, facilitates the integration of theory, practice, and craft. This articulation contributes to the education of socially engaged designers committed to fostering cultural sustainability as a response to the complexities faced by the fashion sector. It is concluded that transdisciplinary approaches, by repositioning fashion design education, promote processes of social innovation and cultural sustainability, providing foundations for a transformative design education rooted in ethical and identity-based cultural practices.
Keywords: fashion design; transdisciplinary; teaching methodologies; cultural sustainability; textile crafts